Ecological risk assessment of a subtropical river influenced by discharges of residues from water and sewage treatment plants - Silva, Angélica Megda; Abessa, Denis [UNESP]; Pamplin, Paulo Augusto Zaitune; Bohrer-Morel, Maria Beatriz (Emerald, 2017)
Purpose: The São Lourenço River (SLR) is used to supply potable waters for the cities of São Lourenço da Serra and Juquitiba, but receives the residues from the water treatment plants (WTPs) and sewage treatment plants (STPs), respectively. The purpose of this paper is to evaluate the impacts of the discharges of Juquitiba’s WTP and STP on the quality of the SLR, by using an integrated approach based on different lines of evidence. Design/methodology/approach: Six sampling sites were established along the river and comprised areas situated upstream and downstream of the discharges. Five sampling surveys were performed between 2004 and 2006 for collecting water and sediment samples for ecotoxicological assays. In two of these campaigns, benthic community structure and geochemistry (metals, nutrients and sediment texture) were also assessed. Findings: Concentrations of P, Fe and Al in waters exceeded the national standards, but sediments were not considered to be contaminated by metals or nutrients. Water and sediments tended to exhibit marginal toxicities, excluding the sediments from JQT007 and JQT008 that were frequently toxic. Combination of geochemistry, toxicity and ecological indices indicated that some sites are not degraded, but in some stations the benthic alteration may be due to non-measured contaminants, especially in JQT007 and JQT008. Practical implications: As the use of waters from SLR for public supply has increased, these results show that action should be taken in order to reverse the environmental degradation of SRL. Originality/value: This research combined sediment and water quality assessments in order to provide a more suitable and reliable diagnostic of the environmental quality of the SLR.
Keywords: Contamination; Ecological risk assessment; Environmental quality; Sediment; Sewage; Water